Mobility of Top Incomes in Germany. (2nd February 2015) - Jenderny, Katharina
Abstract : I analyze German top income mobility using micro‐level panel data of personal income tax returns which are highly representative for top income taxpayers for the years 2001–06. Top income mobility is assessed in three dimensions: (i) persistence in top income fractiles and its stability over time, (ii) measures of individual mobility that are not dependent on the fractile size: the degree of mobility between equally sized groups and mobility in ranks, and (iii) mobility's impact on top income shares. Persistence in top income fractiles is comparatively high and fairly stable across the analyzed period. Top income recipients are less prone to downward mobility and see less variation in annual ranks than less rich tax units. Mobility's impact on income concentration is moderate. The top percentile's share is reduced by roughly 5 percent over six years.